2018
DOI: 10.9734/ajaar/2018/41599
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-agronomical Diversity in Some Sesame (Sesamum indicum L.) Cultivars under Drought Stress Conditions

Abstract: Sesame (Sesamum indicum L.) is a survivor crop. It is one of the most important oilseed crops. Despite of its tolerance, drought is one of the most important environmental factors that limit sesame production. Iran has an arid and semi-arid climate and very fertile lands for agriculture that the main factor limiting production is their lack of water. In this study, the experimental treatments consisted of irrigation levels as the main plot at four levels and fifteen cultivars of Sesame as the subplot was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…SWP was strongly related to NBP, LA, LDW, TDM, PST, CT, and HI under WW and WS, indicating that these traits directly affect sesame SWP. These results are in line with the findings of previous studies (Gharib-Eshghi et al, 2016;Anastasi et al, 2017;Saljooghianpour and Javadzadeh, 2018). A stronger relationship with NBP and NCP indicates that these are important secondary traits contributing to the final SWP of sesame.…”
Section: Association Of Traits With Seed Yield and Selection Of Genotypes For Drought Tolerancesupporting
confidence: 92%
See 1 more Smart Citation
“…SWP was strongly related to NBP, LA, LDW, TDM, PST, CT, and HI under WW and WS, indicating that these traits directly affect sesame SWP. These results are in line with the findings of previous studies (Gharib-Eshghi et al, 2016;Anastasi et al, 2017;Saljooghianpour and Javadzadeh, 2018). A stronger relationship with NBP and NCP indicates that these are important secondary traits contributing to the final SWP of sesame.…”
Section: Association Of Traits With Seed Yield and Selection Of Genotypes For Drought Tolerancesupporting
confidence: 92%
“…The phenotypic and genetic variability of these Indian genotypes for drought adaptability has not yet been estimated using multivariate analysis techniques such as principal component analysis (PCA) and cluster analysis (CA). However, these techniques have been employed in other crops (Gharib-Eshghi et al, 2016;Iqbal et al, 2018;Saljooghianpour and Javadzadeh, 2018) to establish relationships among genotypes, identify superior genotypes (Tabrizi et al, 2011;Dudhe et al, 2018), and explore genotypic diversity (Dudhe et al, 2019). CA has also been used to cluster accessions with similar characteristics into homogenous categories in multidimensional space.…”
Section: Introductionmentioning
confidence: 99%
“…However, G05, G01, G04, and G11genotypes with 6.88, 6.85, 6.81, and 6.56 g had the highest yield per plant under drought stress, respectively. Previous studies on sesame under drought stress revealed a significant reduction in yield per plant and other agro-morphological traits, in line with our results (Kim et al 2006;Ozkan and Kulak 2013;Saljooghianpour and Javadzadeh 2018). Overall, significant variations for yield and other morphological traits were observed among sesame genotype under both drought and normal conditions.…”
Section: Anova Heritability and Means Comparisons Of Morphological Tr...supporting
confidence: 91%
“…The number of capsules was also significantly correlated with the plant height and capsule diameter (p<0.05). Similarly, significant positive correlations of seed yield with plant height, the number of capsules, and the number of seeds per capsule were reported by Saljooghianpour and Javadzadeh (2018). Secondary traits that show a high positive correlation with seed yield are preferred for selection under drought stress (Roy and Basu 2009).…”
Section: Correlation Analysismentioning
confidence: 86%
See 1 more Smart Citation